KORELASI KEPEMIMPINAN KEPALA SEKOLAH DAN DISIPLIN ANTARA GURU TERHADAP KINERJA GURU DI SMP - Lili Suryani; Bambang Sahono; Manap Somantri (Manajer Pendididikan, 2017)
The purpose of this study is to analyze the general school leadership and discipline of work with teacher performance junior high schoolAs the District of STL TerawasUluMusiRawas. The study population was all government school teachers in junior high schoolAs the District STL TerawasUluMusiRawas which amounted to 102 people, with a standard error of 10%, the number of samples from a population of 102 people to 73 people. The conclusions of the research are as follows: First, a significant difference between the Leadership Principal principals on teacher performance by the correlation value of 0.343. Secondly, a significant difference between the performance of teachers Work Discipline by the correlation value of 0.736. Third, there is simultaneously a significant influence between Headmaster Leadership and Work Discipline principals on teacher performance by the correlation value of 0.737.